Perforator-based local flaps for cutaneous facial reconstruction - Khaled Mohamed Abdel Azeem; Sarah Mohamed Abdelghany Abdelaal; Mohamed Fathi Abdel Maguid; Philobater Bahgat Adly Awad; Basma Hussein Abdelaziz Hassan; Wael Mohamed El Shaer; Mostafa Fathy Ibrahim Ahmed (SpringerOpen, 2024)
Abstract Background Despite the advancement of reconstructive surgical techniques, facial defect reconstruction has been always very challenging, aesthetic satisfaction has often been difficult to achieve due to the unique characteristics and complexity of the facial tissue. There have been various options regarding reconstruction and compensation of soft tissue loss all over the body rather than the face. Regardless of whether skin grafts, local flaps, and free flaps were used in the reconstruction process, each of them has its limitations. Beginning with skin grafts results could not always be satisfactory due to contracture, color, and lack of texture Additionally, local flaps have limitations due to mobility and the availability of overlapping skin and tissue, as well as the bulkiness of the pedicle which may need a second staged surgery and lately the difficulty of the free flaps and being a major surgery. Results Patients ages ranged between 23 and 77 years old, with a mean age of 58.33 ± 12.47. As regards the patients' sex, 63.3% of our patients were males and 36.7% were females. Co-morbidities were found in 60% of cases (DM 23.3%, HTN 20%, HCV 3.3%, cardiac 3.3%). Most flaps were facial artery perforator flaps 53.3%, then transverse facial artery 26.7%, superficial temporal artery 10%, angular artery 6.7%, and supra-trochlear artery 3.3%. Twenty-ix cases representing 86.7% of cases went uneventful, while complications showed in 4 cases representing 13.3% of cases, 1 case (3.3%) showed venous congestion that was relieved within 24 h after 2 suture releases, another case (3.3%) showed wound dehiscence that was improved after 2 days with regular dressings, the third patient (3.3%) had recurrence after 4 months that was treated by excision and grafting, while last patient (3.3%) had inadequate excision that was treated by radiotherapy. No bleeding or infection occurred. Also, we observed no correlation between flap length and complications. As regards the functional point of view, all patients showed no functional impairment at the donor site, and only one case showed functional impairment at the recipient site. As regards patient satisfaction, all 30 patients achieved positive satisfaction scores using the Likert scale, 18 cases were satisfied, and 12 cases were very satisfied. Conclusion The use of perforator-based flaps can provide a more effective and aesthetically pleasing solution for the reconstruction of small to moderate facial defects, provided that a reliable Perforator is accurately identified and executed by an experienced surgeon.